Albania : Third Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Review Under Extended Arrangement, and Financing Assurances Review; Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Albania. (IMF Staff Country Reports; Country Report ;, 2007)
Albania's Third Review Under the Three-Year Arrangement under the Poverty Reduction and Growth Facility is analyzed. Albania has reached a pivotal stage in its economic development. Increasing foreign direct investment and rapid financial sector development point to a faster convergence toward the emerging market income levels. The authorities will take revenue measures and use expenditure savings to fully cover the cost of stabilizing the state-owned electricity company's financial position in 2007.These measures should ensure that priority expenditure is protected and budgetary safeguards remain adequate.